2012
DOI: 10.1007/s12205-012-0006-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of MODIS 16 global terrestrial evapotranspiration products in various climates and land cover types in Asia

Abstract: Evapotranspiration (ET), or the sum of water released to the atmosphere from ground surfaces, intercepts canopy precipitation through evaporation and plant transpiration and is one of the most significant components in the water cycle. In this study, Moderate Resolution Imaging Spectroradiometer (MODIS) 16 global terrestrial ET products were validated at 17 flux tower locations in Asia. Overall, overestimations due to energy balance misclosure distorted the trend of the data at nine locations [r: 0.27-0.82; bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(108 citation statements)
references
References 53 publications
9
99
0
Order By: Relevance
“…In order to demonstrate the reliability of the ET dataset in our site, we offer the following points. First, the validity of MOD16-ET has been verified on different scales, as has been shown for Asia [73], Korea [74], China [75], Shaanxi Provence [76] and the Wei River Basin [77]. Second, the synergy between NPP and ET, which has been found in our site by Jia et al [33], means that ET can be enhanced with the increases in NPP.…”
Section: Credibility Of the Resultssupporting
confidence: 72%
“…In order to demonstrate the reliability of the ET dataset in our site, we offer the following points. First, the validity of MOD16-ET has been verified on different scales, as has been shown for Asia [73], Korea [74], China [75], Shaanxi Provence [76] and the Wei River Basin [77]. Second, the synergy between NPP and ET, which has been found in our site by Jia et al [33], means that ET can be enhanced with the increases in NPP.…”
Section: Credibility Of the Resultssupporting
confidence: 72%
“…Nevertheless, it should be noted that the MOD16-NB is not based on in situ measured weather variables, albeit the only public domain 1-km ET product for the study area. Further, previous validation studies [11,28,[48][49][50] also revealed limitations of the product for certain land-cover classes, climate zones and elevation zones. Yet, such a comparison of ET estimates is useful to shed light on differences on ET estimates due to forcing data, model structure and its parameterization.…”
Section: The Mod16-nb-based Evaluationmentioning
confidence: 95%
“…Though progressing significantly in the past years and gaining maturity enough for calibration of hydrological models, remote sensing-based ET products still induce various uncertainties, e.g., [72,73,80]. These uncertainties come in various forms, such as from temperature and net radiation [35], and the aerodynamic component [81].…”
Section: Actual Evapotranspirationmentioning
confidence: 99%